1998
DOI: 10.1046/j.1432-1327.1998.2581009.x
|View full text |Cite
|
Sign up to set email alerts
|

An apyrase from Mimosa pudica contains N5,N10‐methenyl tetrahydrofolate and is stimulated by light

Abstract: An apyrase (NTP/NDPase) implicated in the response of Mimosa pudica to stimuli, such as touch, has been cloned, sequenced and expressed in Escherichia coli. While purifying and characterizing this enzyme, it was observed that a chromophore is associated with it, having absorption in the ultraviolet-A/ blue region of the spectrum. The absorbance maximum of the chromophore, purified from the enzyme complex by gel filtration and HPLC, is around 350 nm. The chromophore has been identified as N5,N10-methenyl tetrah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…An apyrase with a molecular mass of 36 kD was previously isolated from Mimosa, and its primary sequence was reported (Ghosh et al, 1998a). In this study, we isolated MP67 as a novel apyrase by monitoring ADP-hydrolyzing activity; therefore, we did Figure 6.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An apyrase with a molecular mass of 36 kD was previously isolated from Mimosa, and its primary sequence was reported (Ghosh et al, 1998a). In this study, we isolated MP67 as a novel apyrase by monitoring ADP-hydrolyzing activity; therefore, we did Figure 6.…”
Section: Discussionmentioning
confidence: 97%
“…Comparison of hydrolyzing activity toward 14 different phosphate compounds revealed that the enzyme is an NDPase distinct from conventional apyrase (Ishikawa et al, 1984). Isolation and cloning of a 36-kD apyrase from M. pudica have been reported, and this enzyme plays a role in the light response of Mimosa (Ghosh et al, 1998a(Ghosh et al, , 1998b. However, the deduced amino acid sequence of the 36-kD apyrase did not contain an ACR and was quite different from other apyrases (Shibata et al, 2001).…”
mentioning
confidence: 99%
“…However, so far, expression of plant and animal recombinant apyrases in E. coli cells has almost always resulted in formation of inclusion bodies (IB) [2024], with an only exception of Mimosa pudica where soluble and catalytically active apyrase enzyme synthesis has been demonstrated [17, 25]. The reason for the formation of inclusion bodies is usually a toxic effect of synthesized proteins on bacterial cells or incorrect folding of overexpressed polypeptides resulting from limitations of prokaryotic cells in eukaryotic protein synthesis (errors in the synthesis of a polypeptide chain, reducing environmental bacterial cytosol) and/or very high level expression of heterologous proteins (inefficient intracellular mechanisms of polypeptides folding) [26].…”
Section: Resultsmentioning
confidence: 99%
“…Expression of recombinant NTPDases, both plant and animal, in bacterial cells, almost always resulted in the formation of insoluble and inactive aggregates [2024]. Only in the case of M. pudica apyrase, a soluble and catalytically active enzyme was achieved, in addition to IB [17, 25]. Soluble and catalytically active NTPDase also obtained in a prokaryotic system was Lp1NTPDase derived from the bacterium Legionella pneumophila .…”
Section: Discussionmentioning
confidence: 99%
“…4), horse gram , potato (Handa and Guidotti 1996), Arabidopsis and (DDBJ/EMBL/ /GenBank AF093604), mimosa (Ghosh et al 1998) and of an ecto-apyrase from rat (Wang and Guidotti 1996) are shown in Fig. 5.…”
Section: Comparison Of Polypeptide Sequences Of Several Plant Apyrasesmentioning
confidence: 99%